2004
DOI: 10.1128/jb.186.8.2376-2384.2004
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia spp. Alter Pseudomonas aeruginosa Physiology through Iron Sequestration

Abstract: Pseudomonas aeruginosa and members of the Burkholderia cepacia complex often coexist in both the soil and the lungs of cystic fibrosis patients. To gain an understanding of how these different species affect each other's physiology when coexisting, we performed a screen to identify P. aeruginosa genes that are induced in the presence of Burkholderia. A random gene fusion library was constructed in P. aeruginosa PA14 by using a transposon containing a promoterless lacZ gene. Fusion strains were screened for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 50 publications
2
60
1
Order By: Relevance
“…Consistent with those data, we have recently demonstrated that pyoverdine from P. aeruginosa increases the expression of ornibactin synthesis genes by Burkholderia cenocepacia with a concomitant inhibition of growth (Tyrrell et al, 2015). Conversely, Weaver & Kolter (2004) demonstrated using microarray analysis that Burkholderia-conditioned medium and ornibactin induced genes involved in iron regulation in P. aeruginosa strains. However, P. aeruginosa is unable to utilize ornibactin for iron acquisition (Weaver & Kolter, 2004).…”
Section: Pathogen Interactions and Competition For Iron In Cfsupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with those data, we have recently demonstrated that pyoverdine from P. aeruginosa increases the expression of ornibactin synthesis genes by Burkholderia cenocepacia with a concomitant inhibition of growth (Tyrrell et al, 2015). Conversely, Weaver & Kolter (2004) demonstrated using microarray analysis that Burkholderia-conditioned medium and ornibactin induced genes involved in iron regulation in P. aeruginosa strains. However, P. aeruginosa is unable to utilize ornibactin for iron acquisition (Weaver & Kolter, 2004).…”
Section: Pathogen Interactions and Competition For Iron In Cfsupporting
confidence: 66%
“…Conversely, Weaver & Kolter (2004) demonstrated using microarray analysis that Burkholderia-conditioned medium and ornibactin induced genes involved in iron regulation in P. aeruginosa strains. However, P. aeruginosa is unable to utilize ornibactin for iron acquisition (Weaver & Kolter, 2004). Bakkal et al (2010) have reported that bacteriocins produced by Pseudomonas and Burkholderia strains have intra-and interspecies bacteriocin-like inhibition ability within the CF lung (Bakkal et al, 2010).…”
Section: Pathogen Interactions and Competition For Iron In Cfmentioning
confidence: 99%
“…Accordingly, and as previously underlined, infections of the CF airways is highly polymicrobic and there is growing evidence that many of these microorganisms interact (Sibley & Surette, 2011) as observed between P. aeruginosa and S. aureus (Biswas et al, 2009;Hoffman et al, 2006;Mitchell et al, 2010b;Qazi et al, 2006;Yang et al, 2011), P. aeruginosa and Burkholderia spp. (Bakkal et al, 2010;Chattoraj et al, 2010;Riedel et al, 2001;Weaver & Kolter, 2004), P. aeruginosa and S. maltophilia , P. aeruginosa and C. albicans (McAlester et al, 2008), and more generally with a large proportion of the organisms found in the CF airways (Duan et al, 2003;Sibley et al, 2008).…”
Section: Interspecies Interactions Between Cf Pathogensmentioning
confidence: 99%
“…antibiotic resistance | microbial ecology | secondary metabolism | surfactant C ompetition among bacterial species involves the exchange of natural product metabolites, including antibiotics, signals, and toxins (1)(2)(3)(4)(5)(6). Natural products benefit producing bacteria through signaling and inhibitory functions toward competitor bacteria (7)(8)(9).…”
mentioning
confidence: 99%